2011
DOI: 10.1074/jbc.m110.189605
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase Regulates Plasma Membrane Targeting of the Ras-specific Exchange Factor RasGRP1

Abstract: Receptor-induced targeting of exchange factors to specific cellular membranes is the predominant mechanism for initiating and compartmentalizing signal transduction by Ras GTPases. The exchange factor RasGRP1 has a C1 domain that binds the lipid diacylglycerol and thus can potentially mediate membrane localization in response to receptors that are coupled to diacylglycerol-generating phospholipase Cs. However, the C1 domain is insufficient for targeting RasGRP1 to the plasma membrane. We found that a basic/hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 71 publications
3
29
0
1
Order By: Relevance
“…These results suggest that RasGRP1/3 are required for ERK activation in response to SDF1α/CXCR4 signaling, but RasGRP1/3 deficiency does not impair PI3K/AKT signaling in response to SDF1α. Interestingly, RasGRP1 contains a C-terminal plasma membrane targeting (PT) domain that includes a basic/hydrophobic cluster of amino acids shown to interact with phosphoinositides [32], [33]. Therefore, targeting of RasGRP1/3 to the plasma membrane and subsequent Ras activation may be dependent on PI3K activity.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that RasGRP1/3 are required for ERK activation in response to SDF1α/CXCR4 signaling, but RasGRP1/3 deficiency does not impair PI3K/AKT signaling in response to SDF1α. Interestingly, RasGRP1 contains a C-terminal plasma membrane targeting (PT) domain that includes a basic/hydrophobic cluster of amino acids shown to interact with phosphoinositides [32], [33]. Therefore, targeting of RasGRP1/3 to the plasma membrane and subsequent Ras activation may be dependent on PI3K activity.…”
Section: Resultsmentioning
confidence: 99%
“…In the plasma membrane targeting (PT) domain of RasGRP1, a small segment enriched in basic hydrophobic residues, termed the BHC motif, has been identified that binds directly to the plasma membrane enriched in anionic phospholipids [48]. This unstructured basic/hydrophobic cluster can mediate membrane binding by presenting positive charges that electrostatically interact with the strongly negatively charged phosphoinositide headgroups; additionally, it has aromatic and long aliphatic side chains that insert into the lipid bilayer [49, 50, 51, 52].…”
Section: Resultsmentioning
confidence: 99%
“…It is elevated in many cancers either through constitutively active phosphatidylinositol 3-kinase or through inactivation of its degradative pathway as a result of PTEN mutation. The report that RasGRP1 bound PIP 3 through its PT domain [48], which is divergent from that of RasGRP3, suggested that RasGRP3 might show markedly different behavior depending on the membrane environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordination of multiple lipid binding domains to enhance sensitivity to regulation is well recognized for PKC and AKT (49). In Ras-GRP1, for example, the plasma membrane targeter (PT) domain has been described as a key contributor along with the C1 domain (63).…”
Section: Discussionmentioning
confidence: 99%